Thermodynamic modeling of the In–Sc and In–Y systems supported by first-principles calculations - Hu, Zhi; Huang, Can; Tu, Jian; Huang, Yeyan; Dong, Anping (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
Based on an assessment of the phase equilibria and thermodynamic data in the literature, the thermodynamic modeling of the In–Sc and In–Y systems was carried out by means of the calculation of phase diagram (CALPHAD) method supported by first-principles calculations. The solution phases, i.e., liquid, (In), (αSc), (βSc),(αY) and (βY),were modeled with the substitutional regular solution model. 10 intermetallic compounds, includingInSc3, InSc2, In4Sc5, InSc, In2Sc, In3Sc, InY2, InY, In5Y3, and In3Y were described as stoichiometric phases, while In3Y5 was modeled with a sublattice model with respect to its homogeneity range. The enthalpies of formation of the intermetallic compounds at 0 K were computed using first-principle calculations and were used as input for the thermodynamic optimization. A set of self-consistent thermodynamic parameters for both the In–Sc and In–Y systems were obtained and the calculated phase diagrams are in good agreement with the experimental data.